2007
DOI: 10.1021/jf0714463
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effects of a Phenolic Acid Fraction of Rice Bran and Ferulic Acid in C57BL/KsJ-db/dbMice

Abstract: Rice bran contains many phenolic acids, the most abundant of which is the antioxidant, ferulic acid (FA). We evaluated the hypoglycemic effects of a phenolic acid fraction (the ethyl acetate fraction, EAE) of rice bran and of FA in C57BL/KsJ db/db mice. Type 2 diabetic mice were allocated to a control group, an EAE group, or an FA group. Animals were fed a modified AIN-76 diet, and EAE or FA was administered orally for 17 days. There was no significant difference in body weight gain between groups. Administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
155
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 29 publications
3
155
0
2
Order By: Relevance
“…Previous studies of FA treatment describe reduced blood glucose levels (Jung et al, 2007) and weakened lipid peroxide by increasing the antioxidant capacity (Sri Balasubashini et al, 2003). These effects may be a suppression of the ROS by FA treatments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies of FA treatment describe reduced blood glucose levels (Jung et al, 2007) and weakened lipid peroxide by increasing the antioxidant capacity (Sri Balasubashini et al, 2003). These effects may be a suppression of the ROS by FA treatments.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that FA is an antioxidant that neutralizes free radicals such as superoxide, nitric oxide and hydroxyl radicals that may cause oxidative damage to cell membranes and DNA (Kanski et al, 2002;Ha et al, 2008). FA provides meaningful synergistic protection against oxidative stress in the skin and should protect against photoaging and skin cancer (Lin et al, 2005), hypoglycemic and hypolipidemic effects (Sri Balasubashini et al, 2003;Ohnishi et al, 2004;Jung et al, 2007), hypotensive effects (Suzuki et al, 2002), and anti-inflammatory effects (Yagi and Ohishi, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Further study is needed to clarify the exact molecular mechanisms underlying the interaction of ferulate and PI3K/Akt/FOXO3a in aged rats. Ferulate has been reported to increase plasma insulin levels in a model of db/db mice (Jung et al 2007). Different results might come from different circumstances, or pathogenic and normal models.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Ohnishi et al (2004) with KK-Ay mice, the dose of 0.05% FA effectively suppressed blood glucose levels and reduced lipid peroxidation in adipose tissue, indicating that FA may be useful in the reduction of oxidative stress and hyperglycemia in individuals suffering from DM. Subsequently, Jung et al (2007) demonstrated in studies using diabetic mice that FA increases the activity of the enzyme glucokinase, a key enzyme in the regulation of blood glucose levels. Adisakwattana et al (2009) investigated the inhibitory activity of cinnamic acid derivatives against rat intestinal α-glucosidase and porcine pancreatic α-amylase in vitro in order to find effective inhibitors from natural sources that could be used in prevention and treatment of DM.…”
Section: Anti-diabetic Agentmentioning
confidence: 99%